Soil application of Beauveria bassiana GHA against apple sawfly, Hoplocampa testudinea (Hymenoptera: Tenthredinidae): Field mortality and fungal persistence. (2nd September 2015) - Świergiel, Weronika; Meyling, Nicolai V.; Porcel, Mario; Rämert, Birgitta
Abstract: Low impact alternatives to synthetic insecticides for the control of apple sawfly ( Hoplocampa testudinea Klug) are scarce encumbering pest management in organic apple orchards. We investigated the soil persistence and field efficacy of the entomopathogenic fungus Beauveria bassiana (Balsamo) Vuillemin (BotaniGard) against apple sawfly under common organic orchard practices. We also assessed the efficacy of B. bassiana GHA and Metarhizium brunneum Petch (indigenous strain) against sawfly in the laboratory. Larvae treated with either fungus in the laboratory died faster than control larvae and displayed 49.4%–68.4% mycosis. In the field, B. bassiana density remained high in the week after application, during larval descent to the soil. Fungal density decreased to 25% at 49 d after application and to 0.4% after 55 weeks. Molecular markers revealed that the majority of fungal isolates recovered comprised the applied B. bassiana strain GHA. Larvae pupating in soil cages in the orchard for 49 d displayed 17% mycosis. The high efficacy under laboratory conditions was not seen in the field. B. bassiana application resulted in densities above the upper natural background level during the growing season, but reversion to background levels occurred within a year. It remains to be investigated whether this has a detrimental effect on nontarget organisms. Additional work is needed to bridge the knowledge gap between laboratory and field efficacy in orchards.